Floating boat method for carbonate stable isotopic ratio determination in a GasBench II peripheral. (9th June 2021) - Rangarajan, Ravi; Pathak, Pousali; Banerjee, Sanchita; Ghosh, Prosenjit
Abstract : Rationale: Efficient high‐precision stable isotope ratio determination using the GasBench II peripheral for carbonates involves loading of a reaction vial with carbonate powder and injection of phosphoric acid of high density for carbonate digestion. Herein, we present an alternative method, which bypasses the need for acid dosing with an automated pump. The advantages of the new method include minimization of clogging within capillaries caused by the acid, acid spillage, and diffusive fractionation due to repeated piercing of the septa. Methods: The alternative method involves the use of low‐cost boats preloaded with carbonate powder introduced into an Exetainer vial preinjected with phosphoric acid and placed within the compartment of a heated block maintained at a constant temperature in the GasBench II. Results: The new method yielded an improvement in precision for δ 13 CVPDB and δ 18 OVPDB values during replicate analyses of NBS 19, with an overall precision of ±0.04‰ and ±0.06‰, respectively. The accuracy and precision of analysis using the conventional method and the floating boat method were statistically re‐evaluated using a bootstrap error analysis and Monte Carlo simulation methods. Conclusions: The proposed floating boat method of acid digestion showed significant improvement in analytical procedure and overall precision. This method is easily adoptable in other laboratories and is free from frequent issues of needle clogging and irregular fractionation due to diffusion facilitated by repeated puncturing of septa, and can serve as an alternative method for high‐precision carbonate stable isotope analysis.